Nowa antropologia na trzecie tysiąclecie? Nieśmiertelność genetyczna oraz jej moralno-społeczne, ekonomiczne, psychologiczne, pedagogiczne i medyczne konsekwencje = Genetic immortality and its moral social, economical, psychological, pedagogical and medical consequences - Szyszko-Bohusz, Andrzej (1934- ) (Zielona Góra: Wyższa Szkoła Pedagogiczna)
According to the author's Hypothesis of Genetic Immortality the revision of to-date terminology as life, consciousness, personal identity, genetic memory, heredity is proposed. He claims the notion of heredity can be understood as continuity of the parents' life in children. Therefore, the chain of life and consciousness is not interrupted despile of the death of individual. The scientific verification of the Hypothes is of Genetic Immortality creates the new holistic idea on the whole reality, seriously influences the social, economical, psychological, pedagogical and medical spheres of the human activity.
Keywords: antropologia